Kuat Tekan Dan Perubahan Berat Mortar Abu Sekam Padi (Rice Husk Ash) Di Lingkungan Air Gambut - Ednor, Meirisa; Olivia, Monita; Sitompul, Iskandar Romey (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water potentially damage and attack calcium, reduce the strength and accelerate corrosion of mortar and caused significant degradation in the long term. This study aims to determine resistance acid to cement with using added materials were exposed to acidic water. Two types of hardened cementing materials, such as Ordinary Portland Cement (OPC) and Rice Husk Ash (RHA) will be soaked in regular water and peat water. Cement was replace with 15% of rice husk ash. The acid resistance of cements was test by compressive strength, sorptifity, and porosity. There was a considerable decrease in the compressive strength of mortar OPC after exposure to acid attacks from peat water. This research show mortar with rice husk ash was more resistant in peat water for 91 days.Keywords: Acid, Cement, Peat Water, Rice Husk Ash, Resistance.